THE INTEGRAL RURAL TOURISM EXPERIENCE FROM THE TOURIST’S POINT OF VIEW – A QUALITATIVE ANALYSIS OF ITS NATURE AND MEANING - ELISABETH KASTENHOLZ; JOANA LIMA (Tourism & Management Studies)
Rural areas have attracted increasing interest as a space for leisure and tourism, as a result of recent trends in tourism demand, especially from urban populations. However, although the literature on the tourist experience has increased significantly in the past decades, the tourist experience of visiting rural areas remains a relatively understudied field of research. In this context, this paper aims to analyse the nature of the tourist experience in a rural context, focusing on the tourists’ point of view. Concretely, in-depth interviews were conducted with 44 individuals who had visited rural areas, aiming at a deeper understanding of the three phases of the tourist experience: (i) pre (planning, expectations and motivations); (ii) during (events occurred during the visit); and (iii) after the experience (satisfaction, memories and evaluation of the visit). The results show that the countryside is imagined as a space opposed to the negative aspects of the urban space, ideal for resting, recovering forces and living as a family, often associated with the possibility of getting to know the “ancient” and “traditions”. However, results also show that rural tourism destinations should seek alternatives to create a dynamic that attracts/ satisfies tourists without damaging their natural, cultural and social resources.